Recurrent spontaneous haemarthrosis of the knee associated with a synovial and juxta-articular haemangiohamartoma. - Visuri, T (1990)
Several spontaneous episodes of haemarthroses of the knee in a young man led to repeated arthroscopic examinations and one arthrotomy of the affected joint until a juxta-articular haemangiohamartoma was indicated by angiogram. Excision of the malformation stopped the bleeding tendency.